Surgical Benchmarks for ACGME-accredited Adult Reconstructive Orthopaedic Fellowship Training. Issue 20 (15th October 2022) - Silvestre, Jason; Thompson, Terry L.; Wilson, Robert H.; Nelson, Charles L.
Abstract : Introduction: Higher case volumes correlate with improved outcomes in total joint arthroplasty surgery. The purpose of this study was to understand the effect of adult reconstruction fellowship training on reported case volume in a contemporary cohort of orthopaedic surgeons. Methods: The Accreditation Council for Graduate Medical Education provided case logs for orthopaedic surgery residents and adult reconstructive orthopaedic fellows from 2017 to 2018 to 2020 to 2021. Reported case volumes for total joint arthroplasty surgeries were compared using Student t tests. Results: One hundred eighty-three adult reconstructive orthopaedic fellows and 3, 000 orthopaedic surgery residents were included. Residents reported more total hip arthroplasty cases (98.9 ± 30 to 106.1 ± 33, 7.3% increase, P < 0.05) and total knee arthroplasty cases (126.0 ± 41 to 136.5 ± 44, 8.3% increase, P < 0.05) over the study period. On average, fellows reported 439.6 total cases: primary total knee arthroplasty, 164.9 cases (37.5%); primary total hip arthroplasty, 146.8 cases (33.4%); revision total knee arthroplasty, 35.2 cases (8.0%); revision total hip arthroplasty, 33.0 cases (7.5%); unicompartmental knee arthroplasty, 4.4 cases (1.0%); and other, 55.0 cases (12.5%). Overall, adult reconstructive orthopaedic fellowship reported between 1.7- and 2.0-fold more joint arthroplasty cases during 1 year of fellowship training than 5 years of residency ( P < 0.001). Discussion: Adult reconstructive orthopaedic fellowship training provides notable exposure to additional cases after residency training. The results from this study may inform prospective applicants on the effect of fellowship training in total joint arthroplasty and help establish benchmarks in case volume for independent practice.